ON THE TRANSFORMATION PATHWAYS OF α-PBO2-TYPE TIO2 AT THE TWIN BOUNDARY OF RUTILE BICRYSTALS AND THE ORIGIN OF RUTILE BICRYSTALS - Shen P.; Pan C.; Hwang S.-L.; Chu H.-T.; Yui T.-F.; Huang W.-L. (My University, 2005)
Extraction and electron irradiation (under transmission electron microscopy) of an epitaxial nanometer-thick α-PbO2-type TiO2 slab between twinned rutile bicrystals in ultra-high pressure metamorphic rock caused phase changes into a modified fluorite-type and then an amorphous phase. This martensitic-type transition process accounts for the dislocations and stacking faults of the slab and disordering of Ti in the adjoined rutile bicrystals. Additional hydrothermal experiments of sol-gel TiO2-Al2O3 performed at 8.5-9 kbar and 675-800°C in the piston-cylinder apparatus indicated that twinned rutile bicrystals were shaped in mirror image without the formation of α-PbO2-type TiO2 slab at the twin boundary and with no other planar defects for the bicrystals. The twinned bicrystals can be rationalized by growth and/or coalescence processes. Accordingly, it is not justified to assume a precursor phase of α-PbO2-type structure for twinned rutile bicrystals when there is no such relic. Rutile, unless exsolved epitaxially from a host mineral such as garnet, does not constitute evidence for unusually deep burial for ultra-high pressure terranes. © 2005 E. Schweizerbart'sche Verlagsbuchhandlung.
Keywords: α-PBO2-TYPE TIO2; METAMORPHISM; TRANSFORMATION PATH; TWINNED RUTILE; ULTRAHIGH PRESSURE